Tinea gladiatorum due to Trichophyton tonsurans in a school wrestling team in Mexico: A case series - Alexandro Bonifaz; Javier Araiza; Andrés Tirado-Sánchez; Adriana Barbosa-Zamora; Alexander Gómez-Sáenz; Andrea Méndez-Juárez (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Tinea gladiatorum is a type of dermatophytosis that occurs in combat athletes, such as wrestlers and judo fighters, as a result of Trichophyton species. Herein, we aimed to present a small outbreak of tinea gladiatorum in a high school in Mexico. Materials and Methods: Seven individuals belonging to the school fighting team were mycologically studied with direct examinations and cultures. In four cases, T. tonsurans was isolated and identified by morphological and proteomic methods (Matrix-assisted laser desorption/ionization- time-of-flight mass spectrometry). Out of the four subjects, two cases had clinical lesions presented as tinea corporis, and two cases were healthy carriers. Trichophyton tonsurans was also isolated from one of the four training mats (25%). All positive patients were treated with systemic or topical antifungals and achieved clinical and mycological cure. Conclusion: We report the first outbreak of tinea gladiatorum caused by T. tonsurans among a group of high school wrestlers in Mexico.